Parents' Knowledge of Genetic Care and UTI Events in Toddlers in the Children's Ward - Pria Wahyu Romadhon Girianto (Chakra Brahmanda Lentera Institute, 2022)
Background: Infections of the urinary tract caused by bacterial invasion are known as urinary tract infections (UTI). The ability of parents to Genetalia’s care can be seen in how to clean Genetalia, cleaning during urinating or defecating, habits of disposable diaper changing, and habits of anal cleansing. This study aimed to investigate the correlation between the parents' ability to care for their children with the incidence of UTI in toddlers in the children's ward of Amelia Hospital Pare Kediri. Methods: The design used in this study was cross-sectional. There were 81 respondents in the research of toddlers who fulfilled inclusion criteria. This was done using purposive sampling. The independent variables were the parents' ability to take care of their children and the dependent variables were the incidence of UTI in their children. Data was collected using respondent observations. Results: The result showed that almost all respondents have a lack of parents' ability to care for their children (65.4%) and almost all toddlers have an incidence of urinary tract infection (63.3%). After analyzing the data with the cramers v contingency coefficient test and obtaining = 0.000, H1 was accepted and Ho was rejected, indicating that there was a relationship between family support and quality of life. r = 0 to 79. Conclusion: In order to prevent the increasing incidence of UTI, it is recommended that hospitals increase the preventive efforts of ISK events in infants by providing counseling to parents using media such as leaflets, brochures, or video screenings.